Underlying Mechanism of Combined Effect of Methamphetamine and Morphine on Lethality in Mice and Therapeutic Potential of Cooling - Mizuho Namiki; Tomohisa Mori; Toshiko Sawaguchi; Shinobu Ito; Tadashi Suzuki (Elsevier, 2005)
An increase in polydrug abuse is a major problem worldwide. A previous study showed that coadministration of methamphetamine and morphine induced lethality in rodents and humans. However, the underlying mechanisms by which the lethality is increased by the coadministration of methamphetamine and morphine have not been fully understood. Therefore, the present study was designed to determine the mechanism of increased lethality induced by methamphetamine and morphine. Coadministered methamphetamine and morphine increased the lethality by more than 70% in BALB/c mice. Pretreatment with NMDA-receptor antagonists, such as MK-801 and 3-((R)-2-carboxypiperazin-4-yl) propyl-1-phosphonic acid (CPP), and benzamide [poly(ADP-ribose) polymerase (PARP) inhibitor] significantly attenuated the increased lethality induced by methamphetamine and morphine. Furthermore, the lethal effect induced by methamphetamine and morphine was completely attenuated by immediate cooling after the coadministration of methamphetamine and morphine. It has been reported that methamphetamine-induced neurotoxicity can be blocked by lowering the temperature, and this effect might be mediated by a reduction of release of free radicals. These results suggest that activation of NMDA receptors and PARP play an important role in the increased lethality induced by methamphetamine and morphine. Keywords:: methamphetamine, morphine, toxicity, oxidative stress